MSH3 Homology and Potential Recombination Link to SARS-CoV-2 Furin Cleavage Site - Ambati, Balamurali K.; Varshney, Akhil; Lundstrom, Kenneth; Palú, Giorgio; Uhal, Bruce D.; Uversky, Vladimir N.; Brufsky, Adam M. (Frontiers in Virology, 2022)
Among numerous point mutation differences between the SARS-CoV-2 and the bat RaTG13 coronavirus, only the 12-nucleotide furin cleavage site (FCS) exceeds 3 nucleotides. A BLAST search revealed a 100% complementary match to the human mut S homologue (MSH3), which was extended to 19 nucleotides. The reverse complement sequence present in SARS-CoV-2 may occur randomly but other possibilities must be considered. Recombination in an intermediate host is an unlikely explanation. Single stranded RNA viruses such as SARS-CoV-2 utilize negative strand RNA templates in infected cells, which might lead through copy choice recombination with a negative sense SARS-CoV-2 RNA to the integration of the MSH3 negative strand, including the FCS, into the viral genome. In any case, the presence of the 19-nucleotide long RNA sequence including the FCS with 100% identity to the reverse complement of the MSH3 mRNA is highly unusual and requires further investigations.